Peculiarities of the second dozen numerals declination in the Church Slavonic language of Ukrainian edition of the late XVI–VII centuries (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article describes the peculiarities of the second dozen numerals declination in the Church Slavonic language of Ukrainian edition of the late XVI–VII centuries. There has been performed the comparison of the analyzed forms with the corresponding ones in the Old Slavonic and Ukrainian languages XVI–VII of centuries. It has been revealed that the second dozen numerals in the considered texts had already been compound words with the second conjugated component in the most cases. Unlike the Ukrainian language of XVI–VII centuries, the trend of the second numeral component transformation into the affix is not presented among the considered forms.
Keywords: Church Slavonic; second dozen numerals; case forms of the numerals